Compositores e intérpretes cearenses: o campo da música independente no Ceará dos anos 1980 e 1990 - Soares, Aládia Quintella (2015)
This research discuss how the trajectory of the musical group NUCIC – Núcleo de Compositores e Intérpretes Cearenses –, core of composers and performers of Ceará – contributed to produce the first independent music CD of Fortaleza City entitled " Composers and Performers Ceará " in 1993, by this collective. The members of this collective were musicians, mostly born in Ceará, with some characteristics in common; the main perceived one in the development of this research is the fact that most of them had non-formal and informal musical training. In Ceará, before the work of NUCIC, we can verify the presence of other collectives such as “O Pessoal do Ceará" in the 1970s and "Massafeira" in the 1980’s. However, it is remarkble that there is a scant literary output about the Ceará music production in the 1990’s. This study intends to contribute with a register of this movement to changing this situation. The focus of this work is to observe the mid of the eighties and early nineties. However, with the intention of contextualizing this period, it is necessary to pull back and also move ahead in time, as these will help us in the reading. Such a procedure will be connected to the historical context in Ceará and in Brazil. The theoretical foundation is based on authors such as BOURDIEU (2005; 2007); BARBALHO (2005); LIBÂNEO (1986; 1991); ROGÉRIO (2006; 2011), among others that focus on musical training, habitus, training trajectories. This is a case study in which methodologically, texts readings, interviews with members and privileged observers are included. The expected results converge to a reflection on the non-formal and informal musical education, broadening the field of vision about the Ceará music production in the eighties and early nineties.